Non-invasive algorithms for the diagnosis of pulmonary hypertension - Bonderman, Diana; Wexberg, Paul; Heinzl, Harald; Lang, Irene M. (Thrombosis and Haemostasis, 2012)
Precapillary pulmonary hypertension (PH) is diagnosed when mean pulmonary arterial pressure (mPAP) equals or exceeds 25 mmHg and the pulmonary capillary wedge pressure (PCWP) is equal or lower than 15 mmHg. Because both parameters can only be derived from invasive hemodynamic assessment, right heart catheter (RHC) is still a gold standard for the diagnosis of PH. Severe precapillary PH corresponds to pulmonary vascular disease and carries a poor prognosis. Unfortunately, due to a generally low specificity of non-invasive estimates of systolic pulmonary pressure, at least 50% of patients with suspicion of PH need to undergo invasive RHC for exclusion of precapillary PH. Therefore, and also in order to manage the growing number of postcapillary PH due to heart and lung disease in the general population, pulmonary and cardiologic diagnostic algorithms combining multiple parameters have been developed. Recent disease scores are reviewed, and an outlook is given on emerging evidence from the DETECT clinical study holding the promise to non-invasively predict precapillary PH in vulnerable patients. These diagnostic trees help limit unnecessary procedures and help differentiate the current categories of PH. However, one has to keep in mind that the diagnosis of PH is still made by hemodynamic assessment.
Keywords: Diagnosis management; Cardiology; clinical studies